Heterosis for Grain Yield Components in Pearl Millet (Pennisetum glaucum (L.) R. Br.) - BC, PATEL; JS, DOSHI; JA, PATEL (Innovare Journal of Agricultural Sciences, 2016)
An experiment comprised of six male sterile lines and 10 inbred testers of pearl millet and their 60 hybrids was conducted at Regional Research Station, Anand Agricultural University, Anand during July, 2011 for studying the extent of hybrid vigour in F1 for grain yield and its components. None of the hybrids was found significant and negative heterobeltiosis and standard heterosis for days to maturity and plant height. The hybrid ICMA 97111 x J 2526 and JMSA 20041 x J 2340 showed higher magnitude of significant and positive heterbeltiosis for total number of tillers and for productive tillers per plant respectively. The highest magnitude of heterobeltiosis and standard heterosis was recorded in the hybrid ICMA 04999 x J 2490 and ICMA 04999 x J 2433, respectively for the trait ear head length. For earhead girth highest and significant positive heterobeltiosis was observed in the hybrid ICMA 04999 x J 2526. Highest significant positive heterobeltiosis and standard heterosis for 1000 grain weight was observed in the hybrid ICMA 96222 x J 2526 and ICMA 98444 x AIB 11 respectively. For grain yield highest significant positive heterobeltiosis and standard heterosis was observed in the hybrid ICMA 98444 x J 2526 and ICMA 96222 x AIB-2 respectively. For total biomass per plant and stover yield per plant highest and significant positive heterobeltiosis and standard heterosis was observed in the cross JMSA-20041 x J-2526 and ICMA-97111 x J-2340 respectively. For the trait panicle harvest index, highest significant positive heterobeltiosis was observed in the hybrid ICMA 04999 x J 2340, while for total protein content hybrid JMSA-9904 x J 2340 and JMSA-20041 x J 2507 had significant positive heterobeltiosis and standard heterosis respectively.